1976
DOI: 10.1111/j.1600-0765.1976.tb00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Distal oxidative metabolic responses induced by epidermal injury

Abstract: Gingival wounds were created at the left maxillary molar region in young rats. Following injury, contralateral and gingival wound specimens were removed over a 7 day experimental period. Distal (contralateral) and wound gingival oxidative metabolism was activated within two days' after injury. Cytochrome oxidase (mitochondrial), NADH cytochrome c reductase (mitochondrial, microsomal) and NADPH cytochrome c reductase (soluble) activities were significantly greater at the distal site two days after injury than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

1977
1977
1984
1984

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
2
4
1
Order By: Relevance
“…The present study confirms previously published data (Stahl & Tonna 1972, Tonna & Stahl 1973, Andreasen & Skougaard 1975 Fine et al 1974Fine et al , 1976 by demonstrating an effect on distal tissues of the host animal receiving an injury as limited as a gingivectomy. This effect appears to be initiated by the surgical trauma and is manifested by differences in cellular metabolic functions and cellular turnover rates.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study confirms previously published data (Stahl & Tonna 1972, Tonna & Stahl 1973, Andreasen & Skougaard 1975 Fine et al 1974Fine et al , 1976 by demonstrating an effect on distal tissues of the host animal receiving an injury as limited as a gingivectomy. This effect appears to be initiated by the surgical trauma and is manifested by differences in cellular metabolic functions and cellular turnover rates.…”
Section: Discussionsupporting
confidence: 92%
“…Andreasen & Skougaard (1975) recently reported that in the rat, periodontal injuries made at the right maxillary first molars led to a three-fold increase in the number of H'-thymidine (HS-TDR) labeled cells at similar, non-injuxed left first molar regions within 24 hours after injtiry. Increased oxidative metabolic activity within 2 days after gingival injury has also been described at non-injured distal sites in the rat (Fine et al 1974(Fine et al , 1976. Such findings are complementary to those described in general surgery where connectiye tissue remodeling, collagen synthesis, and tensile strength changes have heen reported to occur at distal sites in response to surgical trauma and stress (Houck 1965, Madden & Peacock 1971.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Tbe mirror effect of matrix formation observed at tbe control site in relation to tbe site of injury, is also of interest. Recently we described botb biocbemical and ce:llular responses at sites distal to tbe injury itself (Fine et al 1976, Tonna et al 1977, and one wonders wbetber a distal effect to injury may also be expressed in tbe rates of matrix formation.…”
Section: Clinical Significancementioning
confidence: 98%
“…The purpose of this study was to evaluate the effects of glucocorticoids on gitigival oxidative metabolism at sites of gingival injury, sites distal to injury and at noninjured control sites. This problem emerged as a result of findings demonstrating that 1, gingival injury activated oxidative metabolism at distal (nan-injured) sites (Fine et al 1976); 2, trauma induced an inhibition of the mitotic index two days after injtury at distal and distant sites (Tonna et al 1977); 3, skin incision led to alterations in collagen solubility at sites distal to injury (Peacock 1963); and 4, cortisol injections indace collagen changes similar to those seen at sites distal to skin injury (Houck 1965).…”
Section: Introductionmentioning
confidence: 99%